“Análisis de indicadores financieros de las cooperativas de ahorro y crédito del segmento 3 de la provincia de Chimborazo periodo 2021_2022” - Ante Pallo, Libia Gissela (2024)
This research is based on the analysis of the financial indicators of the savings and credit cooperatives of segment 3 of the Chimborazo province, period 2021-2022. The objective of the research is to analyze the financial indicators of the credit cooperatives of the Chimborazo province for the period 2021-2022, with the application of the CAMEL method. The theoretical foundation is based on the present topic of study such as: COOAC`S, CAMEL method, financial indicators. The research methodology contemplates a quantitative approach, descriptive, documentary and field research type, the instrument applied was the survey in the COAC'S of Chimborazo Province corresponding to segment 3, San Jorge Ltda. San Miguel de Pallatanga Ltda. and Nueva Esperanza Ltda. The CAMEL method was applied for the valuation of the cooperatives with the following indicators: capital, assets, quality of administration, profitability and liquidity, which allowed evaluating the information from the financial statements taken from the SEPS for two periods 2021-2022, obtaining results that allowed knowing the situation of the cooperatives, the following is mentioned: San Jorge, and Nueva Esperanza are having problems in the recovery of the portfolio, meanwhile, San Jorge, San Miguel de Pallatanga and Nueva Esperanza, present a high index in the late payment portfolio of Microcredit portfolio, it is determined that they are having problems in the recovery of microcredit credit portfolio. The San Jorge Ltda. cooperative has deficiencies in the coverage of the problematic portfolio, since it has to consider strategies for the recovery of the non-performing portfolio. The COOAC's have deficiencies in operating expenses, since the entities are allocating fewer resources for the administration of their assets. Administrative efficiency of personnel, the entities are not allocating more resources in personnel to manage their assets. In the ROA, the entities show that they will not be able to generate enough income to strengthen their heritage, while in the ROE San Jorge Ltda. and Nueva Esperanza Ltda. show that they would not have enough resources to cover the remuneration to their shareholders. However, San Miguel de Pallatanga, puts in inherent risks, the capacity to respond to immediate cash requirements from its depositors or reserve requirements.